THE ECONOMIC EFFECTIVENESS OF MODERNIZING THE TRANSPORT NETWORK - Muxtorxujayev Baxtiyor Baxodir ugli (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
Abstract: Modernization of the transport network stands as one of the most pivotal strategies for sustainable economic development. As transportation infrastructure forms the backbone of any nation’s economy, upgrading and optimizing these networks creates direct and indirect advantages that echo throughout all sectors. A well-structured and technologically advanced transport system ensures the smooth, efficient, and cost-effective movement of goods and people, leading to increased productivity, reduced operational costs, and ultimately, greater economic output. The evaluation of economic effectiveness in transport modernization encompasses a multifaceted array of benefits, including but not limited to enhanced logistical efficiency, improved connectivity, the stimulation of ancillary sectors, and broader macroeconomic stability.